A VISUAL REPRESENTATION OF GENDER IN INDONESIAN EFL TEXTBOOKS - Chojimah, Nurul; Widodo, Estu (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
Gender inequality remains a prevalent issue in countries such as Indonesia in many communication and social media. One such medium is EFL textbooks. This qualitative study aimed to investigate how visual gender representation in EFL textbooks and describe social factors contributing to the patterns of the representation. The data for this study were human images in three EFL textbooks for senior high school students in Indonesia published by the Ministry of the Republic of Indonesia. Coding and classifying were the methods of data collection. Three dimensions of discourse—description, interpretation, and explanation—were used as the framework for the data analysis. The current study reveals that females and males are visually represented symmetrically, yet the stereotyping of males and females remains prevalent. Women’s movement might be the backgrounding of the depiction of the two genders in a symmetrical position. However, subtle conventional gender stereotypes are also portrayed in this study.